Make in India : Which Exports Can Drive the Next Wave of Growth? - Anand, Rahul (IMF Working Papers; Working Paper ;, 2015)
Structural transformation depends not only on how much countries export but also on what they export and with whom they trade. This paper breaks new ground in analyzing India's exports by the technological content, quality, sophistication, and complexity of the export basket. We identify five priority areas for policies: (1) reduction of trade costs, at and behind the border; (2) further liberalization of FDI including through simplification of regulations and procedures; (3) improving infrastructure including in urban areas to enhance manufacturing and services in cities; (4) preparing labor resources (skills) and markets (flexibility) for the technological progress that will shape jobs in the years ahead; and (5) creating an enabling environment for innovation and entrepreneurship to draw the economy into higher productivity activities.